Simulation of Automated Irrigation ON-OFF Controller based on Evapotranspiration Analysis - Susilo Adi Widyanto; Achmad Widodo; Achmad Hidayatno; Suwoko . (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Climate change tends to be extreme that have a negative impact on the productivity of agriculture business. An automated system is one attempt to solve the problem. This paper presents the development of ON-OFF controller on automated irrigation system based on evapotranspiration analysis. The input data included: temperature, heat radiation, wind speed and air pressure were used to calculate evapotranspiration using revised Penman Mointeith equation. Furthermore the output of such equation was used for input data of ON-OFF controller end then it was compared with a reference of soil moisture data. The use of ON-OFF controler, a reference of soil moisture is approximated by triangular signal, in which the deviation error can be decreased by reducing discretization sampling time. Sampling time of 0.5 second and 0.005 second yielded the deviation error of 30.5% and 11,1%, respectively.